Curriculum Management in Improving the Quality of Graduates in Thai Pesantren - Syarifah Syarifah; Nur Firdaw Buerahen (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This article aims to examine the implementation of Curriculum Management at Ma'had Al-Bittsat Addiyah Yala, an educational institution in Southern Thailand with a majority Muslim population. The research method employed is a qualitative descriptive approach. The research findings reveal that the implementation of Curriculum Management at Ma'had Al-Bittsat Addiyah Yala commences with curriculum planning, involving the formulation of annual, semester, and teaching plans. The school and the curriculum department collaborate to ensure the smooth execution of the curriculum by integrating elements from both institutional and government curricula. Furthermore, curriculum control is exercised through classroom monitoring, supervision of teacher accommodations, and student dormitory management. Ongoing evaluations, including monthly assessments, teacher evaluations following semester examinations, and assessments of student learning outcomes (both written and oral), are utilized to enhance the curriculum. To support the implementation of Curriculum Management, several facilitating factors have been identified. These include the flexibility to tailor the religious education curriculum to the needs of the institution and students, specialized teacher training aligned with their educational fields, and the availability of adequate facilities and infrastructure. Nevertheless, challenges persist, such as students' reduced interest in religious subjects and crowded student schedules. Therefore, recommendations are proposed to enhance the attractiveness of religious subjects, provide further training for teachers based on their specializations, and improve the efficiency of the class schedule. The outcomes of this research hold significant implications for understanding curriculum management in the context of religious education in Southern Thailand, serving as a foundation for future improvements.